(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This study aims to explore the role played by promotion in improving brand identity with the aim of attracting students who want to join Cirebon Football School. The population of this study includes students who are interested in joining the school, with a total sample size of 200 respondents. Sampling was done through purposive sampling technique using a questionnaire as a tool. The research method used is quantitative with data analysis using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results showed that promotion and brand identity have a positive and significant influence on student interest in joining. This happens because students or potential customers at Cirebon Football School tend to trust and be more interested in a company that has a strong and positive brand identity. Therefore, it is recommended that companies in soccer schools increase promotional efforts and develop various types of promotions to strengthen their brand identity, so as to increase student interest in registering and joining.